Impacts of deglaciation on benthic marine ecosystems in Antarctica (ICEBERGS): JR19002 data ... - Scourse, James; Barnes, David; Meredith, Michael P; Sands, Chester J; Retallick, Kate; Munoz Ramirez, Carlos P; Roman-Gonzalez, Alejandro; Alexandroff, Stella J; Annett, Amber; Blumenroeder, Julian; Bull, Christopher Y S; Butler, Paul G; et al. (NERC EDS British Oceanographic Data Centre NOC, 2022)
The joint UK (NERC) and Chile (CONICYT) ICEBERGS project investigated the physical processes and feedbacks implicated in rapid climate-induced warming deglaciation of three west Antarctic Peninsula tidewater glacier systems, and the impacts of this deglaciation on benthic communities in the adjacent fjords between 2017 and 2020. The project involved three research cruises on the RRS James Clark Ross, JR17001 (ICEBERGS1, November-December 2017), JR18003 (ICEBERGS2, December 2018-January 2019) and JR19002 (ICEBERGS3, January-February 2020). The data from JR19002 are compiled here. The project focused on three sites, Marian Cove (King George Island), Börgen Bay (Anvers Island) and Sheldon Cove (Adelaide Island). Multidisciplinary deployments characterised each cruise, involving: CTD, multi-beam swath bathymetry, TOPAS, water sampling (salinity, oxygen isotopes), LADCP, VMADCP, EK80, Hamon grab, multicore, shelf underwater camera system (SUCS), Agassiz trawl and N70 plankton nets. ...